1079. Casirivimab and Imdevimab (CAS + IMD) Antibody Combination for the Treatment of Immunocomprised Hospitalized Patients with COVID-19. (15th December 2022) - Somersan-Karakaya, Selin; Mylonakis, Eleftherios; Oviedo-Orta, Ernesto; O'Brien, Meagan P; Casullo, Veronica Mas; Mou, Jenni; Xiao, Jing; Bhore, Rafia; Mahmood, Adnan; Hooper, Andrea T; Hussein, Mohamed; Ali, Shazia; et al.
Abstract: Background: Immunocompromised (IC) individuals are at high risk for severe COVID-19, with high morbidity and mortality. CAS+IMD is a monoclonal antibody combination that neutralizes susceptible SARS-CoV-2 variants. We examined the natural history of COVID-19 and the efficacy and safety of CAS+IMD in IC patients (pts) hospitalized with COVID-19. Methods: In a phase 1/2/3 double-blind trial (NCT04426695) conducted Jun 2020 to Apr 2021, prior to the emergence of Omicron-lineage variants, hospitalized COVID-19 pts were randomized 1:1:1 to a single 2.4 g or 8.0 g dose (combined for analyses) of CAS+IMD or placebo (P). Post hoc analyses assessed change in viral load (VL), clinical outcomes (death or mechanical ventilation [MV]), and safety for IC pts with B-cell deficiency or dysfunction (Table 1 ) vs all pts. Results: 99/1940 (5.1%) treated pts were identified as IC (Table 2 ). At baseline, IC vs all pts were more likely to be seronegative for SARS-CoV-2 antibodies (68.7% vs 41.2%), and to have higher median VLs (7.21 vs 6.32 log10 copies/mL). Compared to all pts receiving P, IC pts receiving P had slower VL declines. Treatment with CAS+IMD led to a reduction in VL from baseline, with a least-squares mean time-weighted average change in VL difference vs P at Day 7 for IC pts of -0.69 (95% CI: -1.25, -0.41) vs -0.31 (CI: -0.42, -0.20) for all pts; treatment benefit persisted through Day 29 (Fig. 1 ). Although sample size was small for IC pts, trends in clinical outcomes of death or MV at Day 29 for IC pts (7/64 [11.0%] CAS+IMD vs 6/35 [17.2%] P) were consistent with those in all pts (200/1307 [15.3%] CAS+IMD vs 113/633 [17.9%] P). IC vs all pts treated with CAS+IMD exhibited similar rates of treatment emergent adverse events (TEAEs, 30.4% vs 26.6%), AEs of special interest (grade ≥2 hypersensitivity or infusion-related reactions; 1.4% vs 2.5%), and death (8.7% vs 12.2%; Table 3 ). IC and all pts exhibited fewer TEAEs with CAS+IMD vs P. Conclusion: IC vs all pts hospitalized with COVID-19 were more likely to exhibit high VLs at baseline and to be seronegative. In the study, a single dose of CAS+IMD significantly reduced VL in IC pts (for variants circulating at the time, predominantly Alpha) and resulted in fewer events of death or MV. There were no new safety findings in IC pts vs all study pts. Disclosures: Selin Somersan-Karakaya, PhD, BARDA: Grant/Research Support|Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Eleftherios Mylonakis, MD, PhD, Chemic Labs/KODA Therapeutics: Grant/Research Support|Cidara: Grant/Research Support|Leidos Biomedical Research Inc./NCI: Grant/Research Support|NIH/NIAID, NIH/NIGMS: Grant/Research Support|Pfizer: Grant/Research Support|Regeneron Pharmaceuticals, Inc.: Grant/Research Support|SciClone Pharmaceuticals: Grant/Research Support Ernesto Oviedo-Orta, MD, PhD, MBA, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Meagan P. O'Brien, MD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Veronica Mas Casullo, MD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Jenni Mou, PhD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Jing Xiao, PhD, Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Rafia Bhore, PhD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Adnan Mahmood, MD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Andrea T. Hooper, PhD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Mohamed Hussein, PhD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Shazia Ali, PharmD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Eduardo Forleo-Neto, MD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Gary A. Herman, MD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds Boaz Hirshberg, MD, MBA, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds David M. Weinreich, MD, Regeneron Pharmaceuticals, Inc.: Employement|Regeneron Pharmaceuticals, Inc.: Stocks/Bonds.